USE OF FILM MEDIA IN INCREASING STUDENTS' UNDERSTANDING IN HISTORY LEARNING AT SMAN 1 MEDAN - Pandiangan, Ronaldes; Sumantri, Pulung; Nasution, Imsar Muda (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to explore and analyze the use of film media in increasing students' understanding of history at SMA Negeri 1 Medan. The research method used is qualitative with a case study approach. This research involves direct observation, interviews, and document analysis to gain an in-depth understanding of how the film medium is used and its impact on student understanding. Research findings show that the use of film media can increase student engagement in history learning, relive historical context, and facilitate understanding of complex concepts. Apart from that, student interaction with film media also strengthens information retention and motivates learning. The implication of this research is the importance of considering the use of film media as an effective learning tool in the context of history learning in high schools. The importance of developing students' media literacy is also highlighted in this research. Teachers need to provide systematic teaching on how to analyze, evaluate and understand messages conveyed through film media so that students can become intelligent and critical media consumers. Apart from that, collaboration between teachers, students, parents and the community is also important in supporting the use of film media in history learning. By involving all relevant parties, the use of film media can become an integral part of the school curriculum and make a significant contribution to achieving national education goals. Overall, this research confirms that the use of film media is a potential tool for increasing students' understanding of learning history at SMA Negeri 1 Medan. However, its use needs to be integrated with a holistic approach, paying attention to aspects of media literacy, fair representation and collaboration between stakeholders. In this way, a richer, more relevant and meaningful learning experience can be created for students to understand their historical heritage.